STUDI TENTANG KONSEP AKAR KARAKTERISTIK PADA GERAKAN SPESIFIK SHALAT - Tomi Tristono; Zuhrotul Rumanah (Profetika: Jurnal Studi Islam, 2020)
Specific postural gestures at one rak’ah in Muslim prayer (Shalat) include standing, bowing once, and two prostrations. This phenomenon is a full round of movement. This study is aimed to analyze the mathematical concepts, especially based on the root characteristics of a full round (rotation) of one rak’ah of Muslim prayer (Shalat). This study was conducted with a qualitative approach. It was the liberary research. It compared between the specific postural gestures of Muslim prayer (Shalat) to the round of Thawaf at the Kaaba. This method was used. Then furthermore, the mathematical concepts were analyzed based on their equilibrium points, their characteristic roots, and their orbitals. Muslim prayer (Shalat) is a manifestation of rotation at a single equilibrium point, its characteristic roots are purely imaginary, and it always pass through certain orbitals as long as the parameters do not change. In general, it is said, specific postural gestures at one rak’ah in Muslim prayer (shalat) is the core of the recognition of monotheism to Allah SWT (Al-Ahad) and the faith in Allah SWT as the Unseen (Al-Ghaib).